2014
DOI: 10.1139/cjes-2013-0152
|View full text |Cite
|
Sign up to set email alerts
|

New geophysical models for subsurface velocity structure in the Nechako–Chilcotin plateau from 2.5-D waveform tomography

Abstract: Seismic inversion is applied to generate physical property models (P-wave velocity and numerical attenuation) for four profiles in the Nechako-Chilcotin plateau region of south-central British Columbia, Canada. A newly developed method that combines three-dimensional (3-D) travel-time inversion and 2.5-dimensional (2.5-D) viscoacoustic full-waveform inversion was applied to generate the geophysical models from vibroseis data acquired along the preexisting crooked roads. These models are useful for the characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The relative complexity of the shallow subsurface (strong lateral velocity variations, weathering, etc.) on land complicates even further the inversion of seismic reflection data (Adamczyk et al., 2015; Plessix et al., 2012; Smithyman et al., 2014; Stopin et al., 2014). FWT has largely been limited to 2D data sets with long offsets and, high S/N ratio (Jaiswal et al., 2009; Malinowski et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The relative complexity of the shallow subsurface (strong lateral velocity variations, weathering, etc.) on land complicates even further the inversion of seismic reflection data (Adamczyk et al., 2015; Plessix et al., 2012; Smithyman et al., 2014; Stopin et al., 2014). FWT has largely been limited to 2D data sets with long offsets and, high S/N ratio (Jaiswal et al., 2009; Malinowski et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that seismic full waveform inversion (FWI) provides more detailed information of the subsurface structure [15,[17][18][19][20]. Kamei et al [17] applied the frequency-domain acoustic FWI to long offset marine ocean bottom seismic (OBS) data to image the megasplay fault system of the seismogenic Nankai subduction zone off Japan.…”
Section: Introductionmentioning
confidence: 99%
“…The velocity model from this study clearly shows a low-velocity zone extending laterally over 40 km associated with fluids driven from the downgoing subducting plate, and clearly delineates the accretionary prism from the downgoing Phillipine Sea Plate. In a different study, Smithyman et al [19] applied 2.5-D frequency-domain visco-acoustic FWI to land vibroseis data collected along crooked roads to obtain velocity and attenuation models of the Nechako-Chilcotin plateau of British Columbia, Canada. Models from this study provide important information of the Cenozoic volcanic structures down to 3 km depth.…”
Section: Introductionmentioning
confidence: 99%